Pendampingan UMKM Kopi Indrokilo melalui Literasi Digital untuk Pemasaran Berkelanjutan - Ginting, Rosalina Br.; Adhi, Antono Herry Purnomo; Maryanto Maryanto; Suyoto Suyoto (Pusat Riset dan Inovasi Nasional, 2025)
This community service program is based on the actual conditions experienced by local coffee businesses that face significant obstacles in increasing their sales turnover due to limited knowledge of digital tools. This activity aims to share a better understanding of the digital world with the coffee business community in Indrokilo Hamlet, so that they can apply digital technology continuously and independently in order to improve marketing and increase sales. The method used to achieve the program's objectives is to provide direct literacy training to members of the Kelompok Wanita Tani (KWT) Manggar Lestari through several intensive sessions conducted sequentially and interactively. The results of the literacy program show that training participants increasingly understand and realize the importance of applying digital technology in their business processes to remain competitive. This activity is expected to be the beginning of further sustainable community empowerment efforts on related topics, so that the coffee business community in Indrokilo can continue to develop, innovate and grow steadily.